FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS IN THE PROCESS OF ENGLISH LANGUAGE LEARNING IN HIGHER EDUCATION - Tytarenlp, A.A. (Pedagogy of Higher and Secondary Education, 2010)
Forming of primary class future teachers’ foreign communicative competence in the process of learning English in the higher educational establishment is considered in this article.